Cystatin C and neutrophil gelatinase-associated lipocalin: biomarkers for acute kidney injury after congenital heart surgery (Swiss Medical Weekly, 2013)
QUESTIONS UNDER STUDY: To evaluate the diagnostic value of serum Cystatin C and urine neutrophil gelatinase-associated lipocalin (NGAL) for the detection of acute kidney injury in patients undergoing congenital heart surgery. METHODS: Serial samples of serum Cystatin C and urine NGAL were collected from 139 consecutive patients with congenital heart defects aged 3 days to 30 years after admission to the intensive care unit, 2 and 6 hours after the end of cardiopulmonary bypass. Biomarker levels were compared to perioperative data retrospectively. Acute kidney injury was defined according to the paediatric-modified RIFLE classification. RESULTS: According to the paediatric-modified RIFLE criteria 53% of patients developed evidence of acute kidney injury. Serum Cystatin C concentrations were strongly correlated with severity of acute kidney injury. Optimal sensitivity of 80% and specificity of 66% for the prediction of acute kidney injury occurred at a cut-off value of 0.995 mg/l, 2 hours after the end of cardiopulmonary bypass. The 2 hour urine NGAL concentration was significantly correlated to the duration of cardiopulmonary bypass, time of aortic cross clamping, and serum lactate concentration. Moreover a significant correlation was found between urine NGAL and both length of hospital stay and mechanical ventilation. CONCLUSIONS: In patients after congenital heart surgery, urine NGAL indicates the damaging force of cardiopulmonary bypass and serum Cystatin C is a valuable predictive biomarker for resulting acute kidney injury.